2016
DOI: 10.1016/j.jds.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Chinese dental students' knowledge and attitudes toward HIV/AIDS

Abstract: Background/purpose: Oral care is vital to human immunodeficiency virus (HIV)-positive individuals. As future dentists, it is pertinent that dental students have sufficient knowledge and a positive approach toward this disease. The purpose of this study was to assess HIV/ AIDS-related knowledge and attitudes among clinical dental students in central China. Materials and methods: This survey was conducted on 103 dental students in the final year of a 5-year program. A structured questionnaire with 50 questions e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 40 publications
(63 reference statements)
3
29
2
3
Order By: Relevance
“…Among the 600 of healthcare students, 53% had negative attitude towards HIV/AIDS patients (Table 3). This was in accordance with Li et al who also demonstrated in their study that 94% of healthcare students had overall negative attitude towards HIV/AIDS [19]. Horoun et al found that 85% of the nursing students expressed negative attitude towards people living with HIV [20].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Among the 600 of healthcare students, 53% had negative attitude towards HIV/AIDS patients (Table 3). This was in accordance with Li et al who also demonstrated in their study that 94% of healthcare students had overall negative attitude towards HIV/AIDS [19]. Horoun et al found that 85% of the nursing students expressed negative attitude towards people living with HIV [20].…”
Section: Discussionsupporting
confidence: 89%
“…National AIDS Control Organization (NACO announced that in India, HIV prevalence among gay men was 4% to 9% [5]. HIV/AIDS has major effect on the economic growth of a country, as the young age group (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) is getting affected [6].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a study in Iran [5], only 1% of dental students exhibited positive attitudes toward HIV/AIDS-infected patient treatment, meaning that professional attitudes on this subject remain poor despite the excellent/ good knowledge of students. Furthermore, the fact that increased professional knowledge does not translate to acceptance of HIV/AIDS patients has also been shown in other studies [16][17][18][19].…”
Section: Discussionmentioning
confidence: 72%
“…Nineteenth studies were included to evaluate the attitude of dentists and dental students for dental treatment of HIV/AIDS patients. The results showed that, overall, the estimation of prevalence was 0.421, which means that about 42.1% of them had a good attitude score regarding HIV/AIDS, but 44.8% of dental students had a better attitude than dentists who presented only 38.3% of positive attitude score regarding HIV/AIDS; however, it was not statistically significant [4,[6][7][8][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Assessment Of Knowledge and Attitudes Of Dentists And Dentalmentioning
confidence: 99%
“…Generally, the estimate of prevalence was 0.836, which means that about 83.6% of participants had a good score regarding knowledge of needle-stick injury and possible HIV transmission. However, the estimated prevalence of dental student's knowledge was 0.942, which mean that about 94.2% of dental students had a better knowledge than dentists, with 65.8% of knowledge score [7,19,22,23,25,31,33]. To evaluate the knowledge of HIV transmission by saliva in dental students and dentists, we included five studies, which showed various results (Table 3).…”
Section: Assessment Of Knowledge and Attitudes Of Dentists And Dentalmentioning
confidence: 99%